Globally invasive, withdrawing at home: Aedes albopictus and Aedes japonicus facing the rise of Aedes flavopictus - Chaves, Luis Fernando (2016)
It has been suggested that climate change may have facilitated the global expansion of invasive disease vectors, since several species have expanded their range as tempera tures have warmed. Here, we present results from observa tions on two major global invasive mosquito vectors (Diptera: Culicidae), Aedes albopictus (Skuse) and Aedes japonicus (Theobald), across the altitudinal range of Mt. Konpira, Nagasaki, Japan, a location within their native range, where Aedes flavopictus Yamada, formerly a rare species, has now become dominant. Spatial abundance patterns of the three species suggest that temperature is an important factor influencing their adult distribution across the altitudinal range of Mt. Konpira. Temporal abundance patterns, by contrast, were associated with rainfall and showed signals of density dependent regulation in the three species. The spatial and tem poral analysis of abundance patterns showed that Ae. flavopictus and Ae. albopictus were negatively associated, even when accounting for differential impacts of weather and other environmental factors in their co-occurrence pat terns. Our results highlight a contingency in the expansion of invasive vectors, the potential emergence of changes in their interactions with species in their native communities, and raise the question of whether these changes might be useful to predict the emergence of future invasive vectors.